(untitled) (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
Transitioning toward sustainable energy requires integrated energy systems (IES) to prioritize both emission reductions and enhanced energy efficiency. Traditional dispatch methods often struggle to maximize the flexibility of power-to-gas (P2G) setups and adaptable heat-to-power mechanisms due to rigid physical and environmental constraints. To address this, we introduce an advanced dispatch framework that integrates an adjustable thermoelectric ratio alongside a stepped carbon pricing model. By implementing a tiered penalty for excessive emissions, the framework actively promotes greener operations. Furthermore, we optimize multi-energy utilization by splitting the standard P2G process into a two-phase system featuring an electrolyzer (EL), a methane reactor (MR), and a hydrogen fuel cell (HFC). This is coupled with a variable thermoelectric ratio for both the HFC and combined heat and power (CHP) units, allowing for effective cogeneration decoupling. Simulation results confirm that this approach eliminates wind curtailment, significantly curbs carbon output, and bolsters economic viability compared to standard dispatch techniques.